The The Utilization of Augmented Reality Technology in Improving Conceptual Understanding in Economic Learning: English - Oktavia Indriyani; Intan Fazryatun Khasanah; Endang Herawan; Yopi Nisa Febianti (Journal of Education Technology, 2025)
The difficulty in concretely connecting theory with practice, compounded by the limited use of visual and interactive media, has resulted in low learning outcomes. The purpose of this study was to analyze the use of Augmented Reality (AR) technology in improving students’ conceptual understanding in economics learning at the senior high school level. This research employed a quantitative approach with a Pre-Experimental Design, specifically the One Group Pretest-Posttest Design model. The study population consisted of 66 tenth-grade students. The sample was selected using a non-probability sampling technique. The data were collected through tests, with test items serving as the main research instrument. The data were analyzed using the Paired Sample t-test. The results showed a significant improvement in students’ conceptual understanding after the implementation of Augmented Reality-based learning. The average conceptual understanding test score increased from 62.24 (pre-test) to 85.45 (post-test), with a significance value of p < 0.001. These findings indicate that Augmented Reality can bridge the gap between theoretical concepts and practical implementation in economics learning, while also creating a more immersive, collaborative, and participatory learning experience. The implication of this study is that the application of Augmented Reality technology can serve as an innovative alternative strategy in economics education to enhance students’ conceptual understanding more effectively.